Produksi Enzim Pektinase dari Limbah Kulit Pisang oleh Kapang Aspergillus niger dan Aplikasinya Terhadap Klarifikasi Minuman Fungsional Jahe Lemon - Dyan Yulianti; Maria Marina Herawati (Agricultural Faculty, 2020)
Pectinase enzymes are commercial enzymes that can damage pectin by breaking down polygalacturonate acid into monogalacturonate acid through the release of glycosidic bonds. Pectinase enzymes can be produced from a variety of microorganisms, especially from types of mold such as Aspergillus niger using waste as a substrate like a banana peel. Lemon ginger drink is a functional beverage innovation made from ginger with the addition of lemon to add a refreshing sensation. However, the cloudy, pale, and sedimentary appearance in lemon ginger drink causes a lack of interest in consumers, especially young people. When consuming functional drinks such as lemon ginger, there is turbidity caused by polysaccharides such as pectin. Therefore, enzymatic clarification using pectinase is an effective way to reduce pectin in this drink. This study aims to find out the concentration of Aspergillus niger in producing pectinase enzymes from banana peel waste and its application to the clarification of lemon ginger drinks. The method used in this study was a randomized design group (RAK) consisting of 1 factor, the treatment of concentrations of Aspergillus niger 0 mL, 1 mL, 2 mL, 4 mL, and 6 mL. Then followed by the application of pectinase enzymes produced in the clarification of lemon ginger drink, concentration of 0%; 0,08%; 0,10%; 0,12%; 0,16%; 0,20%; and 0.24%. The Data obtained is analyzed using a printing analysis (ANOVA), and if there is influence, then proceed using BNJ test at a real level of 5%. The results showed that the concentration of Aspergillus niger suspension is best in producing pectinase enzymes of 6 mL, with the enzyme activity of 1.83 U/ml. Then the application of pectinase enzyme in the clarification of lemon ginger drink with a concentration of 0.16% better in improving lower clarity and viscosity of the resulting lemon ginger drink.